Inclusive Economic Growth in Ukraine: The Social Aspect - Skrylnik, Andrey; Skrylnyk, Olena; Kulakova, Svitlana; Byba, Volodymyr (International Journal of Engineering and Technology, 2018)
International human rights standards are based on the idea of participation of everyone in public life on an equal and non-discriminatory basis. The spread of the inclusive growth of the urban economy in Ukraine is not only a reflection of time and an actual vector of economic development in European countries. The current negative tendencies of the formation and development of the labor market in Ukraine are systematized. Â The description of level and structure of employment of the population of Ukraine with inclusiveness, causes of unemployment is given. The number of vacancies for inclusive population by type of economic activity is calculated. It is proved Â that the optimization of managerial approaches to labor market regulation in Ukraine should be based on the European experience of constructing an inclusive-oriented economic environment.Â